Strategi Percepatan Indeks Pembangunan Manusia (IPM) Di Kabupaten Hulu Sungai Utara - Siska Fitriyanti; Herry Azhar Pradana; Muhammad Arief Anwar (Badan Riset dan Inovasi Daerah Provinsi Kalimantan Selatan, 2019)
Hulu Sungai Utara Regency is one of the regency in Kalimantan Selatan that have the lowest HDI rate among other regencies/cities. Over the past few years, the Government of Hulu Sungai Utara Regency has committed and implemented programs related to the dimensions of HDI. Although several indicators of the HDI elements have shown a significant increase, it is still unable move Hulu Sungai Utara Regency from the last place based on HDI. The study aims to identify the factors that cause low HDI scores, analyze programs and supporting capacity of government agencies related to HDI, as well as to propose programs that can improve HDI in Hulu Sungai Utara Regency. This research is descriptive with qualitative approach. Primary data were collected through in-depth interviews with structural officials in the government agencies that were directly related to the that were directly related to the element of HDI. Secondary data was taken from the Annual Report and Strategic Plan of the latest year from the related government agencies. The results of the study show that the main factor of the low Hulu Sungai Utara Regency HDI exist in the economic sector, which is low per capita expenditure. Related programs and supporting capacity of those government agencies are already quite good in efforts to increase HDI. However, it needs to be more focused on increasing EYS and AYS in the education sector, decreasing cases of malnutrition and early marriage in the health sector, as well as increasing economic growth and per capita expenditure in the economic sector. Abstrak Kabupaten Hulu Sungai Utara (HSU) merupakan salah satu kabupaten di Kalimantan Selatan yang memiliki angka IPM paling rendah di antara kabupaten/kota lainnya. Selama beberapa tahun terakhir, Pemerintah Kabupaten HSU telah berkomitmen dan melaksanakan program-program yang berhubungan dengan dimensi pembentuk IPM. Meskipun beberapa indikator dimensi IPM telah menampakkan peningkatan yang cukup signifikan, akan tetapi masih belum bisa merubah peringkat Kabupaten HSU sebagai pemilik IPM terendah di Kalimantan Selatan. Penelitian ini bertujuan untuk mengidentifikasi faktor-faktor yang menyebabkan rendahnya nilai IPM, menganalisis program dan daya dukung SKPD terkait untuk meningkatkan IPM, serta untuk memberikan usulan program dan kegiatan yang dapat meningkatkan IPM. Penelitian ini bersifat deskriptif dengan pendekatan kualitatif. Data primer dikumpulkan melalui wawancara mendalam dengan para pejabat struktural di SKPD yang berkaitan langsung dengan sektor kesehatan, pendidikan, dan ekonomi. Data sekunder berasal dari Laporan Tahunan dan Renstra tahun terakhir dari SKPD terkait. Hasil penelitian menyatakan bahwa faktor utama rendahnya IPM Kabupaten HSU ada di sektor ekonomi, yaitu pengeluaran per kapita yang rendah. Adapun program dan daya dukung SKPD terkait sudah cukup baik dalam usaha meningkatkan angka IPM, hanya saja perlu difokuskan kepada peningkatan HLS dan RLS di sektor pendidikan, penurunan kasus gizi buruk dan pernikahan usia dini di sektor kesehatan, serta peningkatan pertumbuhan ekonomi dan pengeluaran per kapita di sektor ekonomi.